Evaluation Method of 500kV Transformer Bushing Insulation State Based on Active Power Loss. Issue 1 (1st February 2022) - Gu, Zhaoliang; Xu, Ran; Li, Zhen; Li, Xiaolei; Wang, Yaguan; Xu, Wei; Yi, Feng; Gao, Zhixin
Abstract: The bushing is one of the most important components of power transformer, and it is very important to find the internal defects of bushings as soon as possible, effectively and accurately diagnose its insulation state information. In this paper, the active power loss of 500kV transformer bushings have been analyzed, and the insulation state evaluation method based on active power loss is proposed. To verify the feasibility of evaluation method, one abnormal 500kV transformer bushing was selected to analyze its insulation state. The result shows that this method can be used as a powerful complement to tarδ.